2018
DOI: 10.1167/18.9.4
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of exogenous cueing on saccades and reaches

Abstract: Previous studies have shown that eye and arm movements tend to be intrinsically coupled in their behavior. There is, however, no consensus on whether planning of eye and arm movements is based on shared or independent representations. One way to gain insight into these processes is to compare how exogenous attentional modulation influences the temporal and spatial characteristics of the eye and the arm during single or combined movements. Thirteen participants (M = 22.8 years old, SD = 1.5) performed single or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…If the advantage for ipsiversive targets were due to a common sensory processing stage modulated by visual attention, then we should expect a similar delay in manual and saccadic responses. Actually, while fixating, Malienko et al (108) report exogenous cueing effects (about a 10 ms reduction in RTs) in the same order of magnitude for manual and saccadic responses, confirming a common attentional benefit with either response mode. One anonymous reviewer argued that if we subtracted dual-task costs (i.e., the overall difference between pursuit and fixation tasks), we would see facilitation ahead of pursuit in saccadic and manual tasks.…”
Section: The Distribution Of Attention Around the Pursuit Targetmentioning
confidence: 84%
“…If the advantage for ipsiversive targets were due to a common sensory processing stage modulated by visual attention, then we should expect a similar delay in manual and saccadic responses. Actually, while fixating, Malienko et al (108) report exogenous cueing effects (about a 10 ms reduction in RTs) in the same order of magnitude for manual and saccadic responses, confirming a common attentional benefit with either response mode. One anonymous reviewer argued that if we subtracted dual-task costs (i.e., the overall difference between pursuit and fixation tasks), we would see facilitation ahead of pursuit in saccadic and manual tasks.…”
Section: The Distribution Of Attention Around the Pursuit Targetmentioning
confidence: 84%
“…From a purely methodological point of view, social attention abilities have been widely explored by adopting gaze cueing tasks based on manual responses, such as the one employed here. However, in every day social interactions, we tend to explore the surrounding environment around us through eye movements, which can be considered as a more direct and ecological index of visuo-spatial orienting of attention (e.g., Malienko et al, 2018), and can also provide a more fine-grained picture concerning the possible role of social stimuli on social attention (e.g., Dalmaso et al, 2017aDalmaso et al, , 2017b. In this regard, to the best of our knowledge, only Frank et al (2021) analysed fixations when participants were presented with faces of individuals either wearing a face mask or not.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the neurophysiological evidence neither rules out nor confirms the possibility of eye movements being affected by retrieval-based binding processes. However, given some rather distinct pathways for saccade generation opens up the possibility of effector-specificitywhich might be the reason for differences that have been previously observed between manual and eye responses (e.g., for inhibition-related effects, Ding et al, 2016;Eng et al, 2017;Malienko et al, 2018;Taylor & Klein, 2000;in Hick's law, Kveraga et al, 2002;Lawrence et al, 2008;see Proctor & Schneider, 2018, for a review; localization responses to moving targets, Lisi & Cavanagh, 2017; and several other tasks, see Bompas et al, 2017). Moreover, the joint Simon effect (Sebanz et al, 2003) is not observed for saccadic responses (Liepelt et al, 2019), thus raising doubt that all actions are processed in the same way irrespective of the effector involved.…”
Section: Introductionmentioning
confidence: 99%